2022
DOI: 10.3390/nu14091851
|View full text |Cite
|
Sign up to set email alerts
|

Phase Angle and Handgrip Strength as a Predictor of Disease-Related Malnutrition in Admitted Patients: 12-Month Mortality

Abstract: Background: Phase Angle (PhA) value measured by bioelectrical impedance analysis (BIA) could be considered a good marker of the patient’s cell mass and cellular damage. Various studies have shown that the value of PhA is associated with an increased nutritional risk in several pathologies. However, not many studies have focused on the use of PhA as a screening tool in admitted patients. The aim of this study is to evaluate the prognostic value of PhA to determine disease-related malnutrition (DRM) and the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In hospitalized patients, PhA could be used as an additional resource to identify subjects at risk of malnutrition and functionality level. Fernandez-Jiménez et al [ 11 ] established that PhA values of ≤5.4° and ≤5.3° in men and women, respectively, admitted to hospital for different causes, were significantly associated with malnutrition or malnutrition-related diseases, as sorted by the malnutrition universal screening tool (MUST) scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In hospitalized patients, PhA could be used as an additional resource to identify subjects at risk of malnutrition and functionality level. Fernandez-Jiménez et al [ 11 ] established that PhA values of ≤5.4° and ≤5.3° in men and women, respectively, admitted to hospital for different causes, were significantly associated with malnutrition or malnutrition-related diseases, as sorted by the malnutrition universal screening tool (MUST) scale.…”
Section: Resultsmentioning
confidence: 99%
“…According to our findings, PhA could be useful to identify subjects at risk of malnutrition in patients admitted to hospital for different causes (≤5.4° and ≤5.3° in men and women, respectively) [ 11 ], and functionality impairment in patients with acute stroke (men < 5.62° and women < 4.54°) [ 12 ]. These findings suggest that in the hospitalization context, a consideration of PhA to identify subjects with malnutrition and promptly initiate a suitable nutritional therapy should be incorporated to prevent length of stay and associated complications of malnutrition [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the study from Jansen et al [ 29 ] in critically ill patients showed that a decreased standardized PhA (sPhA) increased the possibility for a patient to be diagnosed with malnutrition. Previous studies have also evaluated other nutritional markers, such as HGS as predictors of malnutrition [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al demonstrated that the prevalence of sarcopenia was 48% based on evidence from 5407 COVID-19 patients. Sarcopenia in COVID-19 patients has been recently reported to be associated with increased complications and mortality [ 55 ]. As HGS is a marker of sarcopenia [ 24 ], it is suggested to be used as a prognostic marker of COVID-19 patients [ 54 ] and patients with low HGS on admission should be closely monitored as patients at greater risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Fernandez-Jimenez, et al found that a low SPhA (standardised phase angle)-malnutrition value (SPhA < −0.3) was significantly associated with a higher mortality hazards ratio (HR 7.87, 95% CI 2.56-24.24, p < 0.001). This biological marker could therefore be incorporated among the screening tools and mortality risk assessment in this population (11).…”
Section: Bioelectrical Impedance (Bia)mentioning
confidence: 99%